Feed incorporated with the macroalgae Kappaphycus alvarezii for broiler chickens in the starter phase - Quirino, Sônia Maria de Brito Marques; Quaresma, Débora Vaccari; Dilelis, Felipe; Freitas, Leonardo Willian de; Machado, Cleriston Andrade; Vellozo, Eduardo; Lima, Marcos Fabio de; Lima, Cristina Amorim Ribeiro de (Revista de Ciências Agroveterinárias, 2020)
An experiment was conducted to evaluate the nutrient digestibility, zootechnical performance, and bone quality parameters of broilers fed a diet containing increasing levels of the macroalgae Kappaphycus alvarezii from one to 21 days of age. A total of 150 Cobb 500® broilers were distributed in a completely randomized design with five treatments, six replications, and five birds per replicate. The total excreta collection method was applied from the 15th and 20th day for the metabolism trial. The following bone quality parameters were assessed: the Seedor index, bone strength, and bone ashes. Dry ground macroalgae were added to the feed in the levels 0%, 0.5%, 1.0%, 1.5% and 2.0%; replacing the inert kaolin. Incorporation of Kappaphycus alvarezii did not influence performance parameters, bone quality parameters, or the coefficients of retention for bone ash and phosphorus. As for feed digestibility, decreases (p<0.05) were observed in apparent metabolizable energy and the coefficients of digestibility for dry matter, crude protein, and crude energy with the inclusion of algae. The algae Kappaphycus alvarezii shows potential as an additive in broiler feed, but a possible decrease in digestibility deserves consideration.